Animal performance changes related to time on feed - A. Chestnut; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1977)
We are developing mathematical models to show how feed intake, rate of gain, and feed efficiency change during the finishing period. When finished, the models might be used to predict when to sell cattle to maximize profit or minimize loss, to plan feed inventories, or to predict when animals have reached a desired grade.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen' s Day; 1977; Beef; Animal performance; Feed intake; Rate of gain; Feed efficiency